Jawabanmu

Jawaban paling cerdas!
2014-08-29T21:09:18+07:00
1. (6x kuadrat + 6x + 3x + 3) - (4x kuadrat + 2x + 2x + 1) = 6x kuadrat + 6x + 3x + 3 - 4x kuadrat - 2x - 2x - 1
= 2x kuadarat + 5x +2
2. (30x kuadrat - 18x - 10x + 6) - ( 6x kuadrat + 24x - 2x - 8) = 30x kuadrat - 18x - 10x + 6 - 6x kuadrat - 24x + 2x + 8
= 24x kuadrat - 6x + 14
PAKE CARA 1-4

1. (2x-1) [(x+4) + (x-2)] = (2x-1) (x+4) + (2x-1) (x-2)
2. (3x+2) [(2x+3) + (x+3)] = (3x+2) (2x+3) + (3x+2) (x+3)
3. (2x+5)[(3x-2)+(3x-1)]=(2x+5) (3x-2) + (2x+5) (3x-1)
4. (4x+2) [(2x-1)-(x-4)]=(4x+2) (2x-1) - (4x+2) (x-4)